Diversity and Inclusion in Global Higher Education Lessons from Across Asia - Sanger, Catherine Shea; Gleason, Nancy W. (Springer Nature, 2020)
This open access book offers pioneering insights and practical methods for promoting diversity and inclusion in higher education classrooms and curricula. It highlights the growing importance of international education programs in Asia and the value of understanding student diversity in a changing, evermore interconnected world. The book explores diversity across physical, psychological and cogitative traits, socio-economic backgrounds, value systems, traditions and emerging identities, as well as diverse expectations around teaching, grading, and assessment. Chapters detail significant trends in active learning pedagogy, writing programs, language acquisition, and implications for teaching in the liberal arts, adult learners, girls and women, and Confucian heritage communities. A quality, relevant, 21st Century education should address multifaceted and intersecting forms of diversity to equip students for deep life-long learning inside and outside the classroom. This timely volume provides a unique toolkit for educators, policy-makers, and professional development experts.